Determination of the etiology of pediatric urinary stone disease by multigene panel and metabolic screening evaluation. Issue 4 (August 2021) - Ziyadov, Elnur; Bisgin, Atil; Deger, Mutlu; Akdogan, Nebil; Izol, Volkan; Aridogan, I. Atilla; Satar, Nihat
Summary: Introduction: Urinary tract stone disease (UTSD) is seen with increasing frequency in children, and genetic, metabolic and environmental factors are known to play a role in its etiology. Since it is a genetically heterogeneous disease, we investigated the multigene panel and metabolic evaluation together. Material and method: Forty-eight pediatric patients that underwent surgery for UTSD and were followed up in the Department of Urology of Çukurova University Faculty of Medicine between March 2016 and July 2019 were included in the study. Children with known metabolic diseases were excluded.A detailed history was taken from each patient, and presence of a positive family history was questioned. Blood and urine samples were obtained, and metabolic evaluation was performed. In addition, 2 cc peripheral blood samples were collected from selected patients to perform DNA isolation at Çukurova University Adana Genetic Diseases Diagnosis and Treatment Center. The analysis of the obtained sequence data was performed. Results: Of the 48 children included in the study, 29 (60.4%) were male and 19 (39.6%) were female. The mean age was 60 ± 50 (12-192) months. It was observed that 28 (58.3%) of the patients included in the study had a positive family history.As a result of the next-generation sequencing studies conducted with the multigene panel, a total of 21 clinically significant variants in eight different genes were identified with the bioinformatics analysis on the data on which quality control was performed. The weighted distribution of the 21 variants according to the genes was as follows: five variants (23.8%) in the SLC3A1 gene, four (19%) in SLC6A20, and three (14.3%) in SLC7A9 and SLC26A1 . The clinical reporting of the disease etiology and/or variants with prognostic significance determined as a result of the performed analyses was completed by field experts in accordance with international standards. The visuals of the detected variants are presented in Summary figure. Conclusion: In pediatric cases with UTSD, it is important to determine the underlying metabolic and genetic risk factors in order to prevent recurrence and apply the most effective treatment. Summary Figure Genome browser image of the homozygous pathogenic c.1400T˃C (p.M467T) variant in the SLC3A1 gene. Summary Figure